Analysis of the ego development of the main character in adapting to social reality in the short story the child’s story by charles dickens: a psychoanalytic approach by freud - Mutammima, Fadilah (Maliki Interdisciplinary Journal, 2025)
This study analyzes the ego development of the main character in Charles Dickens’ short story The Child’s Story through Freud’s psychoanalytic approach. The research focuses on how the ego functions as an adaptive mechanism in mediating the impulses of the id, the demands of the superego, and external social reality throughout different stages of life. Using a qualitative descriptive method, the analysis reveals that the character’s ego gradually develops from childhood to old age, balancing instinctual drives with social expectations. The findings show that the ego enables the character to internalize values, delay gratification, manage emotional conflicts, and adapt to shifting realities. Dickens’s use of symbolic narrative structures illustrates the psychological journey not merely through explicit inner conflicts but also through life stages represented by transitions between characters. This study highlights the significance of Freud’s theory of the ego in literary analysis for understanding identity formation and adaptation. Furthermore, it suggests that integrating other psychological frameworks, such as Erikson’s psychosocial theory, may provide a broader perspective on the social influences of ego development.